EARLY DIAGNOSIS GOUTY ARTHRITISDURING THE PRIMARY HEALTH CARE - Kapustianskа A.A. (World of Medicine and Biology, 2013)
GP diagnosis of gouty arthritisshould be installed before the development of significant dysfunction of the joints, in the initial stages of the disease. Early diagnosis of gouty arthritis should be based on the presence of clinical symptoms with laboratory confirmation. Any disease that begins with inflammation of the joints of the foot, necessarily requires the study of uric acid levels in blood serum. That is why the main task of GP doctor is the early diagnosis of gouty arthritis in order to delay complications, preservation of working capacity of patients and improve their quality of life.